Development and experimental investigation of mechanical properties of graphene-based aluminum 6061 alloys. (2021) - Kumar, Nithin; Lokesh, K.S.; Kannantha, Vinayaka; Pai, Raghavendra; Hebbale, Ajit M.
Abstract: The composites of Aluminum alloy-based particulates which are reinforced can be used for many engineering applications like transport and construction sectors where superior mechanical properties like tensile strength, hardness, are mainly needed. Graphene is getting attention in the development of composite since the last decade because of its unique combination of mechanical, electrical, and thermal properties. The research works that have been reported show a significant enhancement in mechanical properties of Graphene-reinforced Al 6061. Al 6061 composite material having Graphene particulates were fabricated successfully by varying wt% of Graphene between 0, 0.25, 0.5, 0.75, 1 wt% using the stir casting method. Mechanical properties like hardness, tensile strength & compression strength have been conducted by Brinell's hardness tester & Universal testing machine (UTM) respectively. The tensile strength of prepared Al 6061 composites is more when compared to base Al 6061 alloy. It can be seen that there is not much difference in the compressive strength & hardness test of the composite material as the Graphene content increases.